Geographically segmented regulation for telecommunications: lessons from experience - Xavier, Patrick; Ypsilanti, D. (Emerald Group Publishing Ltd, 2011)
Purpose – The aim of this paper is to make policy makers and regulators more fully aware of the practical problems and costs involved in implementing geographically segmented regulation. This awareness will be valuable in deciding whether to adopt the approach and, if so, in designing its implementation, i.e. how the scheme's problems will be addressed and costs minimized. Design/methodology/approach – Increasingly, incumbent operators and some regulators have argued that regulatory forbearance should be adopted in geographic areas (usually the more densely populated cities) where facility-based competition is developing. Certainly geographically segmented regulation accords with widespread agreement that regulation should be the minimum necessary. Indeed, a number of countries have implemented the scheme, including Australia, Austria, Canada, Finland, Portugal, Spain, the UK and USA. This paper examines the experience these countries have had in applying geographically segmented regulation. Findings – The lessons from experience in applying geographically segmented regulation suggest that the processes used to determine specific relevant markets are, at present, contentious and problematic in principle, and complex and subjective in practice. The problems/costs relating to the implementation of geographic regulation could erode the stability, certainty and predictability so important in a regulatory regime. Moreover, outcomes are uncertain, especially when looking ahead into an NGN environment. Originality/value – This is the first paper that examines the actual experience of countries that have implemented geographically segmented regulation.